Summer monsoon rainfall variations and its association with atmospheric circulations over Sudan. (15th November 2021) - Alriah, Mohamed Abdallah Ahmed; Bi, Shuoben; Shahid, Shamsuddin; Nkunzimana, Athanase; Ayugi, Brian; Ali, Arfan; Bilal, Muhammad; Teshome, Asaminew; Sarfo, Isaac; Elameen, Ayman M.
Abstract: This work investigates the factors influencing summer (June–September: JJAS) monsoon rainfall variability over Sudan using monthly datasets from multiple sources from 1980 to 2018. Sequential Mann-Kendall, Empirical Orthogonal Function (EOF), composite and correlation analysis were utilized to investigate the spatio-temporal rainfall variability in Sudan, and its associated circulations and teleconnections. Results revealed a significant increase in JJAS rainfall during the study period. The wet condition was found with accompanying convergence winds at low levels and divergence in the upper levels, while the dry conditions were due to the weakening of convergence moisture transport. A hot Sea Surface Temperature anomalies over the Eastern Pacific Ocean (Nino3.4) are associated with dry conditions, whilst cold anomalies are associated with wet conditions. There was correlation between the first EOFs JJAS rainfall and EOFs SSTs teleconnections NINO3.4. IOD, PDO, and NAO, exhibited moderate to strong positive correlations of 62.5% in average. However, the second mode of SSTs teleconnections EOFS revealed a low positive correlation of 46.4% in average, excluding the strong negative impact of NINO3.4–73%. In different regions in Sudan, the influences of NINO3.4 are much stronger in the south, west and central regions (0.71, −0.71 and −0.72). And IOD exhibited much impact in the south and west regions (0.73, 0.74). The southern and western regions had the highest correlation with PDO and NAO. ENSO and IOD also tend to extend summer rainfall season. Therefore, this research serves as the baseline study for further work to examine the impact of SSTs teleconnections on summer rainfall in Sudan (starting, cessation and extremes), thereby providing a reasonable basis for monitoring and predicting similar conditions in the future. Graphical abstract: Image 1 Highlights: Main factors influencing wet/dry rainfall over Sudan were examined. The results show abrupt change in Sudan Rainfall after 1993. Changes in atmospheric circulations modulate the recent rainfall patterns. Influence of Teleconnections ENSO, IOD, PDO, NAO, was mapped out in SR. Pressure systems, winds and SSTs are key roles to understand JJAS rainfall changes.